Rapamycin Inhibits the mTOR/p70S6K Pathway and Attenuates Cardiac Fibrosis in Adriamycin-induced Dilated Cardiomyopathy - Yu, Su-Yang; Liu, Lei; Li, Pu; Li, Jie (The Thoracic and Cardiovascular Surgeon, 2013)
Background The objective of the present study was to investigate whether mTOR is involved in cardiac fibrosis evident in dilated cardiomyopathy, and whether rapamycin provides therapeutic potential for cardiac fibrosis.Methods Forty-five rats were divided into three groups. Fifteen rats in the Adriamycin group underwent 8 weeks of Adriamycin treatment (2.5 mg/kg, twice per week; i.v.) to induce cardiac fibrosis and dilated cardiomyopathy. Fifteen rats in the rapamycin group received rapamycin (2 mg/kg, per day, orally) and i.v. Adriamycin simultaneously for 8 weeks. Fifteen untreated rats served as controls. Cardiac morphology and function were quantified using echocardiography. mTOR and p70S6K1 mRNA expression were assessed using reverse transcription-PCR. Results Collagen volume fraction (CVF) was significantly elevated in the adriamycin group (3.36 ± 0.75) compared with controls (1.51 ± 0.31), whereas mTOR and p70S6K mRNA expression were significantly increased in the adriamycin group (0.68 ± 0.03 and 0.69 ± 0.03) compared with controls (0.38 ± 0.03 and 0.34 ± 0.02). The Adriamycin group was associated with cardiac dilation and decreased contractile function. The rapamycin group showed significantly decreased CVF (1.87 ± 0.45), accompanied with a significant decrease in mTOR and p70S6K mRNA expression (0.42 ± 0.05 and 0.45 ± 0.04) relative to the Adriamycin group. In addition, treatment with rapamycin recovered impairments in cardiac morphology and function.Conclusion The mTOR/p70S6K pathway plays an important role in adriamycin-induced cardiac fibrosis resulting from dilated cardiomyopathy. Rapamycin is a potential therapeutic treatment that can be used to attenuate cardiac fibrosis and improve cardiac function.
Keywords: rapamycin; mTOR/p70S6K; cardiac fibrosis; dilated cardiomyopathy; adriamycin